Cast in flight - Sagara, Michelle, 1963- (Sagara, Michelle, 1963- Chronicles of Elantra., 2016)
"Private Kaylin Neya already has Dragons and Barrani as roommates. Adding one injured, flightless Aerian to her household should be trivial. Sure, the Aerian is Sergeant Moran dar Carafel, but Kaylin's own sergeant is a Leontine, the definition of growly and fanged. She can handle one Aerian. But when a walk to the Halls of Law becomes a street-shattering magical assassination attempt on the sergeant, Kaylin discovers that it's not the guest who's going to be the problem: it's all of the people who suddenly want Moran dar Carafel dead. And though Moran refuses to tell her why she's being targeted, Kaylin is determined to discover her secret and protect her at all costs--even if keeping Moran safe means dealing with Aerian politics, angry dragons and something far more sinister."--